Preparation of spinel ferrites-based flexible electrodes for high electrochemical performances - Infant Francita Fonseka Christopher; Amudhavalli Karuppiah (Chemical Physics Impact, 2024)
In this study, we synthesized two different types of spinel ferrites as CoFe2O4 and NiFe2O4 nanocomposites by thermal decomposition method to improve the performance of supercapacitor research. Numerous physicochemical characterization tests, including X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), High Resolution Transmission Electron Microscopy (HRTEM), Energy Dispersive X-ray Spectroscopy (EDS), UV–Vis DRS, and Fourier Transform Infrared Spectroscopy (FTIR) analyses, have been conducted to investigate the structural, morphological, and elemental composition of the manufactured ferrite electrodes. Three-electrode systems have each been used in the electrochemical investigations for the electrodes utilizing 3 M KOH as the electrolyte. The nickel ferrite and cobalt ferrite nanocomposites had a maximum specific capacitance of 1096 Fg−1 and 836 Fg−1 at a current density of 1 A g−1. A high energy density is also delivered by the assembled symmetric CoFe2O4 and NiFe2O4 nanocomposites. In addition, the nanocomposites exhibit Pseudo capacitance with excellent cyclic stability of 87.4 % and 80.5 % capacitance retention for 5000 cycles. The fabricated CoFe2O4 and NiFe2O4 electrodes showed a strong reduction in the Rct value than the pristine nanocomposites. The materials have demonstrated promising potential as electrodes for energy conversion and storage.